Image Simulation for Mingantu Ultrawide Spectral Radioheliograph in the Decimetre Wave Range–CORRIGENDUM. (3rd July 2015) - Du, J.; Yan, Y.; Wang, W.; Liu, D.
Abstract : In the original publication of "Image Simulation for Mingantu Ultrawide Spectral Radioheliograph in the Decimetre Wave Range, " by Jing Du, Yihua Yan, Wei Wang, and Donghao Liu, there were concerns regarding ambiguity of a few statements. To clarify, the authors have submitted an update regardingTable 6 (p. 12) and the supporting language (p. 13):